The Demography of Censorship: Examining Correlations Between Community Demographics and Materials Challenges in Canadian Libraries - Nyby, Michael J. (Partnership, 2023)
This study examines materials challenges in Canadian libraries as compiled by the Canadian Federation of Library Associations (CFLA) with the intention of identifying demographic trends in patron challenge behaviour. By cross-referencing the CFLA data with five demographic fields from the 2016 Canadian Census of Population (median age, city size, educational attainment level, median income, and political representation), the study aims to determine whether challenges of a certain nature are more likely to occur in communities with certain demographic profiles. The study identifies twenty-two challenge categories derived from user complaints and three ideological alignments of challenges based on the political ideology standards set by moral foundations theory. Though the available sample is too small to draw any definitive conclusions, some strong trends were apparent. The most common challenge types—challenges to racist content and sexual content—are fairly consistent throughout demographic groupings, but notable correlations were found between demographic profiles and challenges related to LGBTQIA+ (lesbian, gay, bisexual, transgender, queer, intersex, asexual, and more) issues. Progressive-leaning communities were far more likely to challenge homophobic/transphobic materials while conservative-leaning communities challenged more LGBTQIA+-positive works. From an ideological standpoint, young communities tend to be the most progressive in their challenge behaviour, while communities with a low level of educational attainment tend to be the most conservative in their challenge behaviour.